2012
DOI: 10.1080/17522439.2011.608434
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth and recovery in people with first episode psychosis: an investigation into the role of self-disclosure

Abstract: The study investigated the relationship of self-disclosure about a psychotic episode to posttraumatic stress symptoms, posttraumatic growth (PTG) and recovery following psychosis. Thirty-four participants who had experienced a first episode of psychosis completed the Impact of Events Scale-Revised, Disclosure of Trauma Questionnaire (a measure of need for, and resistance to, disclosure), a measure of actual self-disclosure, Posttraumatic Growth Inventory and Process of Recovery Questionnaire. The results highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 31 publications
(32 reference statements)
3
65
0
Order By: Relevance
“…Self-disclosure was associated with a higher level of PTG, consistent with previous studies (Currier, Lisman, Irene Harris, Tait, & Erbes, 2013;Pietruch & Jobson, 2011). Furthermore, willingness to share feelings and thoughts remained a significant predictor of PTG after controlling for other variables, whereas the fact that the patient had talked about the event did not; this suggests attitude towards self-disclosure and the content of what the patient talked about (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Self-disclosure was associated with a higher level of PTG, consistent with previous studies (Currier, Lisman, Irene Harris, Tait, & Erbes, 2013;Pietruch & Jobson, 2011). Furthermore, willingness to share feelings and thoughts remained a significant predictor of PTG after controlling for other variables, whereas the fact that the patient had talked about the event did not; this suggests attitude towards self-disclosure and the content of what the patient talked about (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Both described growth through increased appreciation of life, deeper relating to others, and enhanced perception of personal strength and new possibilities. Pietruch and Jobson (2012) found increased self-disclosure was associated with high levels of PTG and recovery and lower levels of trauma symptoms. Talking about the psychotic episode might therefore facilitate constructive change.…”
Section: Introductionmentioning
confidence: 92%
“…Two recent studies systematically research the concept of PTG in FEP (Dunkley, Bates, Foulds, & Fitzgerald, 2007;Pietruch & Jobson, 2012). Dunkley et al (2007) interviewed two people who had experienced FEP and their significant others.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PTG can also express itself as concrete actions whereby people act in new and different ways in the face of trauma (34, 35). Although traumatic experiences are common in people who have experienced psychosis—studies have suggested that up to 98% of people who experienced psychosis were exposed to prior trauma (36), only a few studies investigated PTG in this population (3739). Thus, we still lack the understanding of what might facilitate PTG in these individuals.…”
Section: Introductionmentioning
confidence: 99%